Analysis of SAK EMKM-Based Financial Statements in Micro, Small And Medium Enterprises EM.ES Sidrap: English - Fahira B, Dian; Sahade; Masnawaty (Muhasabatuna : Jurnal Akuntansi Syariah, 2023)
This study aims to determine the preparation of financial statements based on the EM.ES Sidrap Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). Data collection techniques used are observation, interviews, and documentation. The data analysis technique used in this research is descriptive qualitative. As for the population and sample, the population in this study is related to the Preparation of SAK EMKM-Based Financial Statements for Micro, Small and Medium Enterprises EM.ES Sidrap, while the sample in this study is data related to the Preparation of SAK EMKM-Based Financial Statements for Micro-Small Enterprises and Intermediate EM.ES Sidrap in 2021-2022. The results of this study indicate that the financial reports prepared by EM.ES Sidrap are still not in accordance with EMKM's SAK. Recording is done, namely only recording cash disbursements and receipts. Then the information contained in the EM.ES sidrap financial reports is still done manually and simply. The obstacle faced by the owner in making financial reports is the owner's lack of understanding about the preparation of financial reports in accordance with accounting records and the owner thinks that making financial reports is complicated and difficult to understand.